#dudukdirumah / Neesa Ameera Salim - Salim, Neesa Ameera (Faculty of Art and Design, 2021)
Inspired by the current situation and with the newfound time I had during this lockdown, #dudukdirumah artwork was produced. #dudukdirumah reflects the current situation and how everyone plays a significant role to control the pandemic by staying at home. The artwork sends a message that “hey- stay at home, it is not as bad as it sounds!” and how by staying at home should be seen as an opportunity for many positive reasons : to spend time with your loved ones, to learn new skills (e.g. cooking, creative projects), and maybe to improve upon ourselves in ways we never thought were possible. Life needs to go on, so try to add some colours, textures and new perspectives during this challenging times. Paint your home, colour your life and no matter how hard it gets, please let’s just stay at home and stay safe.